The Figure of Pontius Pilate in Josephus Compared with Philo and the Gospel of John - Christian Gers-Uphaus (Religions, 2020)
In this paper, I attempt an approach to the ‘historical Pilate.’ I aim to present the sources referring to him as well as to point out their rhetorical tendencies. However, the approach is selective: whereas all references to Pilate in Philo and Josephus will be addressed, with respect to the New Testament, this study will be based only on the Gospel of John, because its text offers the longest narrative of the Roman trial of Jesus among the Gospels. At the end of each section, the main conclusions are presented. Finally, after discussed all the sources chosen for this work, I will try to depict a picture of the ‘historical Pilate.’